ĐKXĐ: \(x\ge0\)
\(pt\Leftrightarrow\left(2\sqrt{x}-3\right)\left(\sqrt{x}-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x}=\dfrac{3}{2}\\\sqrt{x}=1\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{9}{4}\left(tm\right)\\x=1\left(tm\right)\end{matrix}\right.\)
\(2x-5\sqrt{x}+3=0\)
\(\Leftrightarrow\left(\sqrt{x}-1\right)\left(2\sqrt{x}-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{9}{4}\end{matrix}\right.\)
\(2x-5\sqrt{x}+3=0\Leftrightarrow2x-5\sqrt{x}=-x\)\(\Leftrightarrow\)\(\left\{{}\begin{matrix}2x=0\\-5\sqrt{x}=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\x=0\end{matrix}\right.\)
xậy x=0